CiToS (Cincin Trigonometri Sederhana) Sebagai Alat Bantu Pembelajaran Prasyarat Materi Penjumlahan Vektor - Rahmat Romdana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This is a best practice paper about how to prepare tenth grade science class students (275 students) at SMA Negeri 1 Kota Serang for understanding trigonometry as prerequisite material for vector addition in the physics subject. I have created and used simple learning tool named CiToS (Cincin Trigonometri Sederhana) in my class to teach basic concepts of trigonometry effectively which is needed by students for learning vector addition. To determine the validity of the tool that has been made, validation was carried out by several practitioner. Meanwhile, to measure the effectiveness of the application of the tool, the N-gain value was calculated from the results of the pretest and posttest students. In addition, an analysis of the students’ responses about using of these tools was also carried out. The validation result showed average score of 86% (very good) and the N-gain value from the pretest and posttest result was 0.92 (high). Student responses about using of these tools showed a positive impression. This practice showed that the use of CiToS learning tool can be one of the effective ways to prepare tenth grade science class students for understanding trigonometry as prerequisite material for vector addition.